TUMOR-SPECIFIC IMMUNE RESPONSE AFTER PHOTODYNAMIC THERAPY - Yu. N. Anokhin (Medicinskaâ Immunologiâ, 2016)
Increased incidence of malignancies requires a search for new therapeutic approaches. E.g., photodynamic therapy (PDT) is an effective anti-cancer treatment that involves administration of a photosensitizing dye followed by visible light irradiation of the tumor. Pre-clinical studies have shown that local photodynamic therapy enhances systemic antitumor immunity. Moreover, it is well known that the long-term effects of PDT depend on functioning of intact adaptive immune response. In this context, the immune system plays a fundamental role. Interestingly, the PDT action is associated with stimulation of systemic immune response against a locally treated tumor. In fact, PDT has been shown to effectively stimulate both innate and adaptive immune systems of the host, by triggering the release of various pro-inflammatory and acutephase response mediators thus leading to massive infiltration of the treated site with neutrophils, dendritic cells and other inflammatory cells. PDT efficacy depends, in part, on induction of tumor-specific immune response which is dependent on cytotoxic T lymphocytes and natural killer (NK) cells. The set of specific receptors enables NK cells to recognize surface molecules on the target cells. Expression of the latter molecules is indicative of viral infection, tumor formation, or cell stress (e.g., DNA damage). The NK cells are also involved into various biological processes in the organism, playing a critical role in immune surveillance, thus representing a potential tool for cancer therapy. It was shown that the tumor cells have increased sensitivity to NK cell-mediated lytic action following PDT. In this review, we further discuss potential relationships between PDT and antitumor immune response.